2021
DOI: 10.1038/s41467-021-24495-w
|View full text |Cite
|
Sign up to set email alerts
|

Structure of PDE3A-SLFN12 complex reveals requirements for activation of SLFN12 RNase

Abstract: DNMDP and related compounds, or velcrins, induce complex formation between the phosphodiesterase PDE3A and the SLFN12 protein, leading to a cytotoxic response in cancer cells that express elevated levels of both proteins. The mechanisms by which velcrins induce complex formation, and how the PDE3A-SLFN12 complex causes cancer cell death, are not fully understood. Here, we show that PDE3A and SLFN12 form a heterotetramer stabilized by binding of DNMDP. Interactions between the C-terminal alpha helix of SLFN12 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 45 publications
6
66
0
Order By: Relevance
“…Moreover, SLFN11 activity is not limited to the nucleus [ 133 , 134 , 135 , 137 , 147 ] and it remains to be determined whether cytosolic IHC staining of SLFN11 should be taken into consideration [ 141 , 148 ]. This is particularly relevant to the fact that human SLFN proteins including SLFN5, 11, 12, 12L, 13, and 14 have strong similarity in their amino acid sequence ( Figure 6 B) [ 11 , 149 ] and that some of these SLFN proteins only act in the cytosol [ 149 , 150 ]. Hence, careful examination of the epitopes is important for assessing the specificity of SLFN11 antibodies.…”
Section: Exploiting Slfn11 As a Therapeutic Biomarkermentioning
confidence: 99%
“…Moreover, SLFN11 activity is not limited to the nucleus [ 133 , 134 , 135 , 137 , 147 ] and it remains to be determined whether cytosolic IHC staining of SLFN11 should be taken into consideration [ 141 , 148 ]. This is particularly relevant to the fact that human SLFN proteins including SLFN5, 11, 12, 12L, 13, and 14 have strong similarity in their amino acid sequence ( Figure 6 B) [ 11 , 149 ] and that some of these SLFN proteins only act in the cytosol [ 149 , 150 ]. Hence, careful examination of the epitopes is important for assessing the specificity of SLFN11 antibodies.…”
Section: Exploiting Slfn11 As a Therapeutic Biomarkermentioning
confidence: 99%
“…C-terminally truncated rabbit and human SLFN14 (residues 1–400) were shown to bind ribosomes and cleave rRNA ( 43 , 44 ). Other studies showed cleavage of tRNA and rRNA by rat Slfn13 (rSlfn13), human SLFN13, mouse mSlfn8 and human SLFN12, suggesting a role in translational regulation ( 42 , 45 ). Recently, Garvie et al.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Garvie et al. presented that a tetrameric complex of two phosphodiesterases PDE3A and two SLFN12 molecules lead to a cytotoxic response in cancer cells ( 45 ). The small molecule DNMDP stabilized binding to PDE3A and increased the RNase activity of SLFN12, which was important for its cytotoxic function.…”
Section: Introductionmentioning
confidence: 99%
“…SLFN12 is stabilized by interaction with Phosphodiesterase 3A (PDE3A) and is recruited and binds the ribosomes to exclude signal recognition peptides and subsequently inhibits translation [ 83 ]. In addition to these effects, SLFN12 has recently been identified as an RNAse that digests ribosomal RNA [ 84 ].…”
Section: Functions Of Human Schlafens In Cancermentioning
confidence: 99%